The American journal of sociology. - University of Chicago. (AJS, 1895)
Established in 1895 as the first U.S. scholarly journal in its field, AJS remains a leading voice for analysis and research in the social sciences, presenting work on the theory, methods, practice, and history of sociology. AJS also seeks the application of perspectives from other social sciences and publishes papers by psychologists, anthropologists, statisticians, economists, educators, historians, and political scientists.
Established in 1895 as the first U.S. scholarly journal in its field, AJS remains a leading voice for analysis and research in the social sciences, presenting work on the theory, methods, practice, and history of sociology. AJS also seeks the application of perspectives from other social sciences and publishes papers by psychologists, anthropologists, statisticians, economists, educators, historians, and political scientists.
Available also online.
Vols. 1-52, 1895-1947. 1. v.; Vols. 1-70, 1895-1965. 1 v.; Vols. 71-75, 1965-70. 1 v.
Keywords: Sociology / Periodicals.; Social sciences / Periodicals.